2019
DOI: 10.1016/j.paid.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence and problematic online behaviors among adolescents: The mediating role of mindfulness, rumination, and depression

Abstract: Preliminary studies have shown that trait emotional intelligence (trait EI) can be a risk factor for higher problematic use of specific online activities. However, the possible mediating role of mindfulness and rumination on the relationship of trait EI with problematic social media use (PSMU) and problematic online gaming (POG) is unclear. Among a sample of 470 adolescents, the present study examined the direct and indirect associations of trait EI with PSMU and POG and the potential mediational role of mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 63 publications
9
41
0
3
Order By: Relevance
“…The Turkish form of SDHS comprises three items (e.g., "I felt that life was meaningless") on a 4-point Likert scale (from "never" to "often") that assesses individual's levels of depressive feelings (Joseph et al 2004). Former studies have reported optimal validity and reliability of the Turkish form (Kircaburun et al 2019). The scale also showed high internal consistency in the present study (0.88).…”
Section: Short Depression-happiness Scale (Sdhs)supporting
confidence: 51%
“…The Turkish form of SDHS comprises three items (e.g., "I felt that life was meaningless") on a 4-point Likert scale (from "never" to "often") that assesses individual's levels of depressive feelings (Joseph et al 2004). Former studies have reported optimal validity and reliability of the Turkish form (Kircaburun et al 2019). The scale also showed high internal consistency in the present study (0.88).…”
Section: Short Depression-happiness Scale (Sdhs)supporting
confidence: 51%
“…Moreover, all of these studies were only conducted with cross-sectional data. The same limitation of the cross-sectional design was observed among the limited studies ( N = 3) on trait emotional intelligence and IGD [17,19,31], although all three studies consistently found a negative association between trait emotional intelligence and IGD among adolescents/students. To our best knowledge, no published study has reported the longitudinal effects of trait emotional intelligence on IGD.…”
Section: Introductionmentioning
confidence: 71%
“…Given its high prevalence and negative consequences (e.g., poor academic performance and sleep problems) [6,12,13,14,15], researchers have been allocating increasing attention to identifying the risk and protective factors of IGD [16]. Emotional intelligence was recently proposed as a potential protective factor [17,18,19,20], but only cross-sectional research has tested its buffering effects. We aimed to fill the current research gap by conducting a one-year longitudinal study to determine whether emotional intelligence is a predictor of IGD.…”
Section: Introductionmentioning
confidence: 99%
“…Rumination—a type of undesirable reaction—is closely associated with mental health problems such as depression, anxiety, and suicide attempts [ 14 ]. Additionally, some studies have found that rumination is directly positively associated with internet addiction [ 15 , 16 ]. Thus, we can speculate that self-control and rumination are both proximal factors that contribute to smartphone addiction before going to sleep.…”
Section: Introductionmentioning
confidence: 99%